APLIKASI PRESENSI KEHADIRAN GURU DI SMKN PAKISJAYA BERBASIS FACE RECOGNITION MENGGUNAKAN OPENCV - Ceme, Didakus; Faizah, NM; Koryanto , Lucky (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
The research objective was to design a teacher attendance application that has a camera feature to take pictures during teacher absences so that it can simplify and speed up attendance requests for absences from work, leave, permission and illness. The prototype method is used as a tool to develop a model into a system with stages which include; gathering requirements, building prototypes, evaluating, coding attendance systems, conducting testing, evaluating, and finally using presence applications to see the functions of the applications being built. The results of this study have produced a prototype of teacher presence at SMKN Pakisjaya based on face recognition using OpenCV and implementing the Local Binary Pattern Histogram (LBPH) as an algorithm for detecting faces from images.